Fungicide Sensitivity of Phaeomoniella chlamydospora, the Causal Organism of Petri Grapevine Decline - Groenewald, M.; Denman, S.; Crous, P.W. (South African Journal of Enology and Viticulture, 2017)
Twelve fungicides, benomyl, chlorothalonil, fenarimol, fosetyl-Al, iprodione, kresoxim-methyl, mancozeb, metalaxyl, prochloraz manganese chloride, quintozene, tebuconazole and thiram were screened in vitro for their ability to inhibit mycelial growth of Phaeomoniella chlamydospora, the causal organism of Petri grapevine decline.  Isolates of Pa. chlamydospora were obtained from different geographical areas in the Western Cape province.  The effective concentration at which 50% of mycelial growth was inhibited (EC50) was calculated for each fungicide.  Benomyl, fenarimol, kresoxim-methyl, prochloraz manganese chloride and tebuconazole were the most effective in inhibiting mycelial growth of Pa. chlamydospora with ECso values ranging from 0.01 to 0.05 μg/mL. Data obtained in this study represent the base-line sensitivity of local isolates to these fungicides, which is important for monitoring the development of pathogen resistance to fungicides.